The Effects of Tai Chi Exercise on Physical and Psychological Functioning in Stroke Patients at the Rehabilitation Stage: A Scoping Review - Nimas Efa Amanah; Meira Erawati; Fitria Handayani (Indonesian Journal of Global Health Research, 2025)
Research on the effects of Tai Chi on physical and psychological functioning in stroke patients has been conducted by previous researchers. However, so far there are limited reviews on this topic. The purpose of this review is to get an overview of the extent of the effects on physical and psychological functions in stroke patients based on the results of studies that have been conducted. Method The keywords used in the article search is “Tai chi” AND “Stroke” AND “Psychological stroke” AND “Stroke rehabilitation” were analyzed using a synthesis matrix. Several databases used in this study such as Scopus (n = 187), Pubmed (n = 17), Sciendirect (n = 3,234) and EBSCO (n = 548) were then eliminated and screened into 10 articles reviewed. The review method uses a scoping review, determining the research questions to be reviewed using the PICO framework (Population, Intervention, Comparison, Outcome). Based on the results of the analysis of 10 articles, it was found that Tai Chi has an influence in helping to reduce symptoms and improve physical and psychological conditions in stroke patients, including on physical function, are increasing motor function (upper and lower extremities), muscle strength, cardiopulmonary, trunk posture, increasing swallowing ability, increasing mobility disorders, sleep disorders and balance control, while on psychological functions are post-stroke depression, reducing symptoms of anxiety and stress, cognitive function in stroke and QOL. The conclusion of the journal review shows that tai chi has an effect on improving physical and psychological conditions and quality of life in stroke patients.